Changement de topique et prise en charge énonciative : le rôle de toujours est-il que - Véronique Lenepveu (Discours)
This article follows a first paper (Lenepveu, 2015) which provided an aspectual and diachronic analysis of the French lexicalized expression toujours est-il que in continuation of Hansen (2004) and Buchi (2007). It was shown that the lexicalized expression marks a return to the main discourse topic (Van Dijk, 1976; Fraser, 2009a and b) and simultaneously that it reinforces the speaker’s commitment. The present paper deals with two distinct uses of the locution: a study of the sentences preceding the locution makes it possible to explain in which contexts toujours est-il que indicates the speaker’s high commitment (Dendale & Coltier, 2005) towards the propositionnal content’s validity or towards the content’s relevance. Then, a search of English synonyms in translations of litterary texts (French/English; English/French) of the 19th and the 20th century confirms the analysis. It appears that toujours est-il que is translated by an epistemic modality marker (it is certain that, certain it is that) when it indicates a difference of degree of belief.